STUDI PENERAPAN REGULASI PENYEDIAAN FASILITAS UMUM DAN FASILITAS SOSIAL DI KLUSTER APARTEMEN GREEN BAY PLUIT - Agustin, Laura Tri; Tresani, Nurahma (Jurnal Muara Sains, Teknologi, Kedokteran dan Ilmu Kesehatan, 2024)
Indonesia is experiencing very rapid development and urbanization. In line with this, in the 90s the government and private sector began to develop housing from housing cluster to apartment clusters. Public facilities and social facilities are one of the requirements regulated by regulations and must be fulfilled by the developer. However, in its implementation, the provision of public facilities and social facilities experiences many obstacles, especially in apartment. The aim of this research is to identify the process of implementing public facilities and social facilities regulations and identify the root causes of the obstacles that occur in implementing public facilities and social facilities in apartment in Jakarta.  To realize this goal, researchers conducteda study of the regulations used and the process of implementing these regulations by developers in DKI Jakarta. This research has the character of an exploratory study and an instrumental case study approach where the researcher will focus on an issue or theory which is then supported by the case study. The instruments used in this research has the character of an exploratory study and an instrumental case study approach where the researcher will focus on an issue or theory which is then supported by the case study. The instruments used in this research were in-depth interviews, documentation and observation. The case study is a high density apartment cluster to see whether the regulations used are in line with the reality on the ground. The case study used is the Green Bay Apartment in North Jakarta with a total of 34.048 people divided into 12 apartment towers. The research results show that the regulations used to date have not been adjusted since 2015 and apartment occupancy regulations still use housing regulations, so that with very high density these regulations are not appropriate. Apart from that, until now public facilities and social facilities are considered private zones of apartments, so they are often not handed over to the government. Keywords: Apartment; Regulation; Facilities; Public; Social Abstrak Indonesia mengalami perkembangan dan urbanisasi yang sangat cepat. Seiring dengan hal tersebut, maka tahun 90-an pemerintah dan swasta mulai melakukan pengembangan hunian dari kluster perumahan hingga kluster apartemen. Fasilitas umum dan fasilitas sosial merupakan salah satu syarat yang diatur oleh regulasi dan harus dipenuhi oleh pengembang. Namun dalam penerapannya, penyediaan fasilitas umum dan fasilitas sosial mengalami banyak kendala, terutama pada hunian apartemen. Tujuan dari penelitian ini adalah untuk mengidentifikasi proses penerapan regulasi fasilitas umum dan fasilitas sosial dan mengidentifikasi akar permasalahan dari kendala yang terjadi dalam penerapan fasilitas umum dan fasilitas sosial pada hunian apartemen di DKI Jakarta. Untuk mewujudkan tujuan tersebut, peneliti melakukan kajian terhadap regulasi yang digunakan dan proses penerapan regulasi tersebut oleh pengembang di DKI Jakarta. Penelitian ini bersifat studi eksploratif dan pendekatan instrumental case study dimana peneliti akan memusatkan perhatian pada suatu isu atau teori yang kemudian didukung studi kasus. Instrumen yang digunakan dalam penelitian ini adalah wawancara mendalam, dokumentasi dan observasi lapangan. Adapun studi kasus yang dipilih adalah kluster apartemen dengan kepadatan yang tinggi untuk melihat apakah regulasi yang digunakan sesuai dengan realita di lapangan. Studi kasus yang digunakan adalah kluster apartemen Green Bay di Jakarta Utara dengan jumlah 34.048 jiwa yang terbagi dalam 12 tower apartemen. Hasil penelitian menunjukkan bahwa regulasi yang digunakan hingga saat ini belum mengalami penyesuaian sejak tahun 2015 dan regulasi hunian apartemen masih menggunakan aturan perumahan, sehingga dengan kepadatan yang sangat tinggi maka regulasi tersebut tidak sesuai. Selain itu, hingga saat ini fasilitas umum dan fasilitas sosial dianggap sebagai zona private dari apartemen, sehingga sering kali tidak diserahkan kepada pemerintah.